Novel protective retrieval device for a large rectal cancer specimen resected by endoscopic submucosal dissection. Issue 6 (9th July 2021) - Inoue, Takahiro; Shichijo, Satoki; Nakajima, Kiyokazu
Abstract : Watch a video of this article.